Comparison of Two Diffusers in a Transonic Centrifugal Compressor. (2003) - Nakagawa, Koji; Hayami, Hiroshi; Keimi, Yuichi
Abstract : Flow mechanisms suppressing the flow separation in two diffusers, a low-solidity cascade diffuser and a vaned diffuser with additional small vanes near the inlet, were compared mainly by numerical simulation. As the superiority of the low-solidity cascade diffuser was expected, a series of experiments was conducted using a transonic centrifugal compressor with a maximum pressure ratio of 7. The performance of the compressor with the vaned diffuser was comparable to that of the low-solidity cascade diffuser only between the surge point and the design flowrate at a pressure ratio of 3.5. The maximum flowrate of the vaned diffuser was lower than that of the low-solidity cascade diffuser. At higher rotational speeds, the pressure ratio at the surge point, the efficiency, and the flow range of the low-solidity cascade diffuser exceded those of a vaned diffuser at a pressure ratio of 3.5.